The Effect of Price Earning Ratio, Debt to Equity Ratio, Dividend Payout Ratio on the Value of the Company the Financial Sector Banking Sub-Sector Listed on the IDX - Gustindy Reza Akbar; Fuad Ramdhan Ryanto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to examine the effect of price earning ratio, debt to equity ratio, and dividend payout ratio on the value of the company in the financial sector banking Sub sector listed on the Indonesia Stock Exchange. Using saturated sampling, a total of 38 financial sector companies were obtained. This study uses a quantitative approach with analytical techniques used are classical assumption test, multiple linear regression analysis, multiple correlation coefficient analysis (R), coefficient of determination analysis (R2), F test and t test. The results showed that the price earning ratio and debt to equity ratio had a positive but insignificant effect on the value of the company, while the dividend payout ratio had a positive and significant effect on the value of the company. These findings suggest that the presence of dividend payout ratio plays an important role in increasing the value of the company.